The effect of strategic performance measurement system on self-efficacy and creativity from levers of control perspectives / Nurulhuda Mohd Nafi, Rozainun Abdul Aziz and Zarinah Abd Rasit - Mohd Nafi, Nurulhuda; Abdul Aziz, Rozainun; Abd Rasit, Zarinah (Faculty of Accountancy, 2019)
Strategic Performance Measurement System (SPMS) have gain attention and become the debatable subject among the academician particularly in 21th century. Generally, the purpose of SPMS is help managers to define and achieve strategic objectives, drives motivation and attitude toward achieving strategic goals and ultimately generate superior performance. Even though SPMS provide comprehensive coverage of importance aspect of business operation for managers to perform decision making, however, recent studies on negative effect of SPMS was been critics for several reasons including creating tension which brought to negative behavior particularly reducing self-competence among the managers, stifle innovation that resulted manager unable to be creative in performing their business activities finally lead to poor company performance. Surprisingly, some evidence provides no effect on organizational performance. In response this, academician have devoting attention on the extensive research on the development of performance measurement system and highlighting its roles as strategic development and its implementation for better organizational performance. Nevertheless, the knowledge on the SPMS use in practice the role in supplying information for decision making on individual motivation and creativity provided ambiguous results. Thus to fill the gap, this study developing the model in explaining of how the effect of SPMS on job performance by using Simons lever of control framework via interactive and diagnostic use of SPMS promote motivation and creativity among the member of organization. By applying self-efficacy theory, this study propose that SPMS use can increase self-efficacy and creativity thus enhance job performance.